Calidad de Vida En La Adaptación De Lentes De Contacto En Pacientes Con Problemas Refractivos Altos Y De Baja Visión (2021)
Low Vision is a multifactorial condition that affects at least 25% of the world's elderly population, affecting more frequently in Asian countries, followed by Eastern countries. Low Vision patient is considered when visual acuity (VA) is less than 0.3 in the better eye and a visual field less than 20 ° (1). This work will intend to establish the changes in the quality of life of patients with high refractive errors and Low Vision, using LC contact lenses versus ophthalmic lenses by means of a literature review. To do this, a search and analysis of articles and literature references was developed in databases such as: Access Medicine, PubMed, Virtual Health Library, and Virtual Library for Public Health surveillance, Imbiomed, SciELO - Scientific Electronic Library Online, Medigraphic, where it is evidenced that LC adaptation improves VA, peripheral field and quality of life of patients.